2017
DOI: 10.3906/sag-1611-67
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid malignancy risk in different clinical thyroid diseases

Abstract: Background/aim: To evaluate the malignancy risk of thyroid nodules in different clinical thyroid diseases. Materials and methods:Patients who underwent thyroidectomy between 2007 and 2014 were grouped as euthyroid, hypothyroid, and hyperthyroid. Further classification was made depending on the presence of solitary/multiple thyroid nodules.Results: Among 2870 patients, 1719 (59.9%) were euthyroid, 962 (33.5%) were hyperthyroid, and 189 (6.6%) were hypothyroid. Overall malignancy was detected in 980 (34.1%) pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
0
10
0
1
Order By: Relevance
“…33 Although rates as low as 2.3% was reported in some previous studies, 6 recent studies revealed much higher rates reaching to 13.7%. 33 Although rates as low as 2.3% was reported in some previous studies, 6 recent studies revealed much higher rates reaching to 13.7%.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…33 Although rates as low as 2.3% was reported in some previous studies, 6 recent studies revealed much higher rates reaching to 13.7%. 33 Although rates as low as 2.3% was reported in some previous studies, 6 recent studies revealed much higher rates reaching to 13.7%.…”
Section: Discussionmentioning
confidence: 83%
“…A wide range of prevalence of malignancy in hyperthyroid patients was reported in the literature. 33 Although rates as low as 2.3% was reported in some previous studies, 6 recent studies revealed much higher rates reaching to 13.7%. 34 The prevalence of malignancy in hyperthyroid patients is beyond the scope of our study, however the possibility of an existing tumor before RAI can not be excluded completely.…”
Section: Discussionmentioning
confidence: 85%
“…However, in a previous study from our center, the malignancy rate in TNG and TMNG patients was 24.7%. 19 The number of studies evaluating TRAb in patients with TMNG is limited. Pederson et al found positive TRAb in 97 of 106 patients with Graves, 15 of 94 with TMNG and 1 of 100 healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…While there are many factors that contribute to the carcinogenesis of the thyroid gland, TSH is considered a key cancer growth factor for thyroid cancer. 8 9…”
Section: Introductionmentioning
confidence: 99%